As you can see in this picture we have a point on y- axis which is our y-intercept and f(x)
so first we should find what WAS the y-intercept before adding k
so we can say:
f(x) = 2(0) - 3 = -3
so it WAS -3 .... but in this picture is -7
so you have:
-3 + k = -7
k = -7 + 3 = -4
so k is equal to -4 :)))
i hope this is helpful
have a nice day
In an inverse proportion two veriables are inversely proportional to each other.You can write the equation as P=n/x, and N is the constant of proportionality.In the equation the X increases and the P decreases.
A parabola is a quadratic function, and a quadratic can be expressed in vertex form, which is:
y=a(x-h)^2+k, where (h,k) is the vertex (absolute maximum or minimum point of the quadratic)
In this case we are given that (h,k) is (-5,80) so we have so far:
y=a(x--5)^2+80
y=a(x+5)^2+80, we are also told that it passes through the point (0,-45) so:
-45=a(0+5)^2+80
-45=25a+80 subtract 80 from both sides
-125=25a divide both sides by 25
-5=a, so now we know the complete vertex form is:
y=-5(x+5)^2+80
The x-intercepts occur when y=0 so:
0=-5(x+5)^2+80 add 5(x+5)^2 to both sides
5(x+5)^2=80 divide both sides by 5
(x+5)^2=16 take the square root of both sides
x+5=±√16 which is
x+5=±4 subtract 5 from both sides
x=-5±4 so the x-intercepts are:
x=-1 and -9
Answer:
D)
Step-by-step explanation:
Each longitude has a time difference of 4 minutes.
Convert 4 hours into minutes
4 hours * (60 minutes/1 hour) = 240 minutes
Divide 240 minutes by 4 to obtain the difference in longitude
240/4 = 60
Answer:
A and E
Step-by-step explanation:
Given
20x² - 26x + 8 = 0 ( divide through by 2 )
10x² - 13x + 4 = 0
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 10 × 4 = 40 and sum = - 13
The factors are - 5 and - 8
Use these factors to split the x- term
10x² - 5x - 8x + 4 = 0 ( factor the first/second and third/fourth terms )
5x(2x - 1) - 4(2x - 1) = 0 ← factor out (2x - 1) from each term
(2x - 1)(5x - 4) = 0
Equate each factor to zero and solve for x
2x - 1 = 0 ⇒ 2x = 1 ⇒ x =
→ E
5x - 4 = 0 ⇒ 5x = 4 ⇒ x =
→ A